Recreational function of Middle Pomeranian forests - Parzych, Krzysztof (Journal of Education, Health and Sport, 2017)
The subject of the study was the description of the recreational function of the State Forests in the Central Pomerania area. An analysis of the recreational potential of the State Forests in 11 poviats of Central Pomerani a was conducted, with an indication of the main forms of tourism and recreation. The development of the area of Central Pomerania State Forests from the point of view of forms of tourism and recreation that could be implemented in their area was also analyzed. As the source material was used to query the resources of the website www.czaswlas.pl. and individual field observations. Analysis of the obtained results indicates the important role of tourism and recreation infrastructure in the management of the Central Pomeranian State Forest’s area. At the same time, there are large spatial disparities in the distribution of particular elements of tourist and recreational infrastructure. The areas of the State Forests of the poviats are the best ones: bytowski, drawski, słupski and szczecinecki, the least urban poviats of Slupsk and Koszalin, białogardzki, and sławieński